Construcción e instalación de un equipo para determinar la relación entre la altura dinámica y el caudal en electrobombas periféricas - Espinoza Gonzales, Janeth Gulnara (2023)
The realistic general of the present work of thesis was: determining the relation between the dynamic height and the flow in a peripheral electric pump, coming true ad hoc the design and construction of a team, the one that they came true in nine (9) performance testings, the one by means of which the experimental values of the flow and the dynamic height of her were obtained of the electric pump TWP13706. When the polynomial regression of second degree made said experimental values, the following equation was obtained: ?EB = 0.0031??2 ? 1.016?? + 35.544, R2 = 0.9972, which acts for the acquaintance between the dynamic height and the flow for the electric pump TWP13706, being ?? and ?EB the produced flow and the dynamic height for the electric pump TWP13706, which express themselves in L/min and m, respectively. The value of the coefficient of determination (R2 = 0.9972), indicate a tall degree of correlation between the dynamic height and the flow, because said values fit to from near-perfect way a polynomial equation of second degree. In like manner, the obtained results show that the minimum and maximum residue between the experimental values and adjusted values of dynamic height are: 0.0198 m and 0.6719 m, respectively, which corresponds to the following percentages of error: 0.06 % y 4.48 %. Then, it can be said that the present investigation is somewhat diligent, with quantitative focus and I design correlational. In this way the present work of thesis is concluded, coming true with the realistic general and in turn trying on his general hypothesis.